Gene Therapy for HIV Infections: Intracellular Immunization - Alain Piché (Canadian Journal of Infectious Diseases)
Despite significant advances in the treatment of human immunodeficiency virus (HIV) infection in the past 10 years, it remains an incurable disease. The inability of traditional drug-based therapies to inhibit HIV replication effectively for extended periods of time has stimulated intense research to develop novel approaches for this disease. Current understanding of HIV molecular biology and pathogenesis has opened the way for the development of gene therapy strategies for HIV infections. In this context, a number of intracellular immunization-based strategies have been evaluated, and some of them have reached the stage of phase I/II human clinical trials. These strategies include the use of single-chain antibodies, capsid-targeted viral inactivation, transdominant negative mutants, ribozymes, antisense oligonucleotides and RNA decoys. While a number of issues remain to be studied before intracellular immunization can be applied to the treatment of HIV infections, the significant progress already made in this field is likely to lead to clinical applications.